2006
DOI: 10.1007/s10894-006-9041-6
|View full text |Cite
|
Sign up to set email alerts
|

On the Physics of Improved Confinement During Pulsed Poloidal Current Drive in MST Reversed-Field Pinch

Abstract: Reduction of core-resonant magnetic fluctuations and improved confinement in the Madison Symmetric Torus reversed-field pinch (MST RFP) have been routinely achieved by applying the surface poloidal electric field. The created inductive poloidal electric field drives current in plasma which leads to the improved confinement. To study the effect we developed a relatively simple 1-D model in cylindrical geometry which assumes poloidal and axial symmetry during the drive. We use resistive magnetohydrodynamics mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…While this is similar to the conclusions of Ref. 19, we show that it is also consistent with pinching due to loss of dynamo, which can dominate the subsequent profile evolution, as discussed in Ref. 17.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…While this is similar to the conclusions of Ref. 19, we show that it is also consistent with pinching due to loss of dynamo, which can dominate the subsequent profile evolution, as discussed in Ref. 17.…”
Section: Introductionsupporting
confidence: 92%
“…The subsequent stabilization is similar to the effect of edge current noted in Ref. 19. However, slightly later in our nonlinear simulation, non- local profile changes due to loss of dynamo begin to occur, and the gradient in the -profile near the rational surface builds.…”
Section: -4supporting
confidence: 81%
See 2 more Smart Citations
“…This study is an addition to the previous modelling of stabilization of core resonant (resonance surface is within the reversal surface) current-driven modes in RFP during PPCD [14,15] which explained their stabilization during the drive. The previous and present studies demonstrated stabilization of current-and pressure-driven modes during PPCD, thus explaining the significant improvement in plasma confinement.…”
Section: Introductionmentioning
confidence: 64%